Islam and development exploring the invisible aid economy - Clarke, Matthew 1969-; Tittensor, David (Ashgate Publishing Limited, 2014)
The study of Islam since the advent of 9/11 has made a significant resurgence. However, much of the work produced since then has tended to focus on the movements that not only provide aid to their fellow Muslims, but also have political and at times violent agendas. This tendency has led to a dearth of research on the wider Muslim aid and development scene. Focusing on the role and impact of Islam and Islamic Faith Based Organisations (FBOs), an arena that has come to be regarded by some as the 'invisible aid economy', Islam and Development considers Islamic theology and its application to development and how Islamic teaching is actualized in case studies of Muslim FBOs. It brings together contributions from the disciplines of theology, sociology, politics and economics, aiming both to raise awareness and to function as a corrective step within the development studies literature